Social support from different sources and its relationship with stress in spaceflight analog environments - Bell, Suzanne T.; Anderson, Steven R.; Roma, Peter G.; Landon, Lauren Blackwell; Dev, Sheena I. (Frontiers in Psychology, 2025)
While there is a large body of research on social support in traditional work settings, less is known about how the unique context of long-term isolation and confinement affects perceived social support. The purpose of our research was to examine how perceptions of social support change over time, how they differ by source (i.e., public, organization, family/friends/colleagues, and other crewmembers), and the relationship between social support and stress. We collected data from 64 crewmembers in five spaceflight analog campaigns with restricted communication with outside sources. Results suggested that perceived social support declined over time for all sources, with declines more pronounced for external sources (public, organization, family/friends/colleagues) than for perceived support from other crewmembers. While perceived overall social support was unrelated to stress over time, social support from crewmembers was related to the stress levels reported by crewmembers in the evening. Our results are important as they: (a) empirically document the decline in perceived social support over time in extended isolation; (b) provide evidence for the critical importance of the role of fellow crewmembers in being able to provide social support in conditions of extended isolation and communication delay; and (c) underscore the need to more fully understand the dynamics between the crew and external sources of social support (public, organization, family/friends/colleagues) as well as how those relationships may be best supported for individuals who live and work in long-term isolation and confinement.